Perioperative chemotherapy with FOLFOX in resectable gastroesophageal adenocarcinoma in real life practice: An AGEO multicenter retrospective study. Issue 12 (December 2016) - Mary, Florence; Zaanan, Aziz; Boige, Valérie; Artru, Pascal; Samalin, Emmanuelle; Coriat, Romain; Bachet, Jean-Baptiste; Boubaya, Marouane; Benallaoua, Mourad; Tougeron, David; Afchain, Pauline; Locher, Christophe; et al.
Abstract: Purpose: Perioperative chemotherapy with 5-fluorouracil and cisplatin, with or without epirubicin, improves overall survival in resectable gastroesophageal junction and gastric adenocarcinoma. The aim of this retrospective multicenter study was to evaluate the safety and efficacy of perioperative chemotherapy with a FOLFOX-based regimen. Patients and methods: We enrolled patients with resectable gastric or gastroesophageal adenocarcinoma, who had at least 3 cycles of a pre-operative FOLFOX-based regimen. The primary end point was the feasibility of the peri-operative chemotherapy. Results: We enrolled 109 patients from 2007 to 2012 in 12 centres. Their median age was 66, 67% were men and 73% had gastric tumours. The median number of chemotherapy courses was 6 with a median of 4 pre-operative cycles and 2 post-operative cycles. Twenty-three patients received at least 8 cycles of chemotherapy. In univariate analysis, the Karnofsky index at inclusion was the only factor associated with 8 cycles of chemotherapy. An R0 resection was achieved in 100 patients (95.2%). Conclusion: The FOLFOX-based perioperative regimen achieves favourable results in real life practice. The optimal number of chemotherapy cycle remains to be determined. FOLFOX regimen may be used as an alternative treatment option to a cisplatin-based regimen in resectable gastroesophageal adenocarcinoma. A prospective randomized trial is needed to confirm these results.